2009
DOI: 10.2353/ajpath.2009.081141
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Aortic Cellular Constituents during Thoracic Aortic Aneurysm Development

Abstract: The present study tested the hypothesis that changes in the resident endogenous cellular population accompany alterations in aortic collagen and elastin content during thoracic aortic aneurysm (TAA) development in a murine model. Descending thoracic aortas were analyzed at various time points (2, 4, 8, and 16 weeks) post-TAA induction (0.5 M CaCl 2 , 15 minutes). Aortic tissue sections were subjected to histological staining and morphometric analysis for collagen and elastin, as well as immunostaining for cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
52
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 45 publications
(45 reference statements)
5
52
0
Order By: Relevance
“…The immunostaining results revealed that MT1-MMP was localized in a cellular pattern similar to what was seen and previously reported with DDR2 (Fig. 6, top and middle, respectively) (19,20). Fig.…”
Section: Aortic Dilatation and Taa Formationsupporting
confidence: 83%
See 2 more Smart Citations
“…The immunostaining results revealed that MT1-MMP was localized in a cellular pattern similar to what was seen and previously reported with DDR2 (Fig. 6, top and middle, respectively) (19,20). Fig.…”
Section: Aortic Dilatation and Taa Formationsupporting
confidence: 83%
“…Previous work from this laboratory (19) has demonstrated that endogenous fibroblasts produce MMP-9 during early aortic dilatation. In addition, degeneration of the elastic architecture was found to occur concomitantly with the emergence of a population of fibroblast-derived myofibroblasts (20). Moreover, upon isolation of aortic fibroblasts from control and TAA-induced mice, it was determined that the TAAinduced fibroblasts had undergone a significant phenotypic change during TAA formation, resulting in an enhanced proteolytic gene expression profile, including a twofold increase in MT1-MMP expression (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MiR-29 was additionally shown to induce apoptosis in cancer cells by targeting Mcl-1, an antiapoptotic Bcl-2 family member, 16 and by augmenting p53 levels. 17 Smooth muscle cell apoptosis is considered to favor aneurysm formation 18 and, because miR-29 is highly expressed in smooth muscle cells (Online Figure V and VII), this mechanism may contribute to miR-29 -mediated destabilization of the vascular wall. Interestingly, inhibition of miR-29 decreased the expression of matrix metalloproteinase MMP9 in the aorta (Online Figure VIII), which may additionally prevent further degradation of matrix proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Degradation of elastin is a key feature of aneurysm development, and extensive clinical and experimental evidence demonstrates that an imbalance between the proteinases and their endogenous inhibitors influences the development and progression of arterial aneurysms. 38 Matrix metalloproteinase 9 appears to be a key factor affecting this balance, with increased activity found in aneurysmal tissue taken from patients with an abdominal aortic aneurysm and MS, 39 in the coronary arteries of children with fatal KD, 30 and in ani- Figure 8. Inhibition of TGF-␤ increases MMP-9 activity and reduces plasminogen activator inhibitor-1 in LCWE-treated mice.…”
Section: Discussionmentioning
confidence: 99%